SISTEM INFORMASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) UNTUK PENINGKATAN LOYALITAS PELANGGAN DI CAHAYA MANDIRI AUDIO & ELEKTRONIK - Wildan Setiawan; Aprilisa Arum Sari; Dwi Hartanti (Universitas Methodist Indonesia, 2026)
Cahaya Mandiri Audio, an electronic service provider, is currently facing operational challenges due to its reliance on a manual record-keeping system, which has resulted in a data error rate of 15% and difficulties in maintaining customer loyalty. This study aims to design and build a web-based Customer Relationship Management (CRM) system capable of integrating customer data management, service history, and technician scheduling to optimize operations and improve customer retention. The development method used is the Prototype approach, utilizing the PHP programming language and the Laravel framework. The results of the study indicate that this system successfully unifies the roles of Admin and Technician within a single integrated platform, thereby minimizing human error and creating a more organized workflow compared to the previous manual system. The contribution and novelty of this system lie in the Scheduled Notification Module via WhatsApp, which facilitates the semi-automatic creation of message drafts through a redirect feature based on unit service history data to efficiently enhance customer loyalty.Keyword: CRM, Service, Laravel, Customer Loyalty, WhatsApp API.